Model Hidrograf Akibat Perubahan Tataguna Lahan DAS Batang Kuranji (Studi Kasus Sub DAS Danau Limau Manis) - Elvi Roza Syofyan; Amrizal Saidi -; Bambang Istijono -; Revalin Herdianto - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2017)
The purpose of the study is to look at changes in land use and hydrograph models of Danau Limau Manis Sub-watershed using data 2011 until 2015.The results shows the change of land use of Batang Kuranji Watershed, Sub DAS Danau Limau Manis can decreased 3.03% from 2011 to 2015. It due to the opening of new land. While shrub rose rose 0360%, because was due of changes of forests that have not done processing. For an others using of the land the number increase 3.40%. It due to changes of forests and shrubs into failure land.. As the runoff coefficient (C) does not occur any significant change that is from 0.405 into 0.408. Peak discharge calculated by the Nakayasu method 128.02 m3 / dt, was greater by Rational method of 127,52 m3 / dt is caused no difference in the approach used.